Momordica and Pycnogenol Can Tolerate Imazamox Induced Toxicity in L929 Cells Line: In Vitro Study - Ali Taghizadehghalehjoughi; Betul Cicek (Proceedings, 2018)
Undesirable side effects that result from the random use of herbicides in developing countries are widespread. Imazamox is a widely used herbicide and has toxic effect on humans. Momordica charantia has been reported to possess many benefits and medicinal properties. Pycnogenol (PYC) is a natural plant extract from the bark of Pinus pinaster Aiton and has potent antioxidant activities. The aim of this study was to evaluate the protective effects of pycnogenol and momardica on induced imazamox toxicity effects on L929 fibroblast cell line. L929 fibroblast cells were cultured in the appropriate culture medium. Toxic concentration of imazamox 250 μM, were administered 30 min prior to momordica and pycnogenol (10−1–10−5 concentration) on L929 fibroblast cell line for 24 h. The cell viability assay was determined by using MTT test. TAC-TOS analysis were used to evaluate antioxidant and oxidant status. According to our study pycnogenol high dose showned protective effect whereas momordica low dose showned protective effect p < 0.05. In current study pycnogenol increased TAC capacity in high dose but in lower dose pycnogenol did not show any promise (p < 0.05). Momordica results showed correlation with MTT result. According to this analyse momordica only in low dose increased anti oxidant capacity and in addition, only in low dose TOS level were decreased (p > 0.05). In conclusion momordica and pycnogenol showed promise to reduced imazamox toxicity.